Antonio Gramsci e le avanguardie di inizio Novecento. Intersezioni con il pragmatismo italiano e europeo - Chiara Meta (Laboratoire Italien)
This essay reconstructs a number of the historical-philosophical sources, extraneous to the tradition of Marxist thought, that came together to form the biography of the young Gramsci. It is here hypothesized that the particular itinerary of Gramsci’s Marxism, which came to be defined as anti-determinist, may have been influenced by certain philosophical currents (United States and European pragmatism, French post-positivist epistemology) outside the tradition of the Second and Third Internationals. In attempting to challenge a certain revision of Marxism belonging to late nineteenth-century positivism, the young Gramsci made use of theoretical equipment that belonged to epistemology, together with pragmatist psychology, which taken as a whole allowed him to retrace and relaunch the theoretical status of Marx’s philosophy.